2013
DOI: 10.1371/journal.pone.0058963
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic Cromones Inhibit Histamine and Eicosanoid Release from Activated Human and Murine Mast Cells by Releasing Annexin A1

Abstract: Background and PurposeAlthough the ‘cromones’ (di-sodium cromoglycate and sodium nedocromil) are used to treat allergy and asthma, their ‘mast cell stabilising’ mechanism of pharmacological action has never been convincingly explained. Here, we investigate the hypothesis that these drugs act by stimulating the release of the anti-inflammatory protein Annexin-A1 (Anx-A1) from mast cells.Experimental approachWe used biochemical and immuno-neutralisation techniques to investigate the mechanism by which cromones s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 66 publications
5
43
0
Order By: Relevance
“…38 A recent publication also reported that cromolyn inhibited PGD 2 release from hCBMC stimulated by IgE/Anti-IgE by 100%. 42 It is, therefore apparent that cromolyn can inhibit the release of histamine and arachidonic acid products, but not cytokines, whether due to IgE/anti-IgE or SP stimulation. In contrast, lut and methlut are more effective MC inhibitors than cromolyn regardless of the trigger and the mediator measured.…”
Section: Discussionmentioning
confidence: 99%
“…38 A recent publication also reported that cromolyn inhibited PGD 2 release from hCBMC stimulated by IgE/Anti-IgE by 100%. 42 It is, therefore apparent that cromolyn can inhibit the release of histamine and arachidonic acid products, but not cytokines, whether due to IgE/anti-IgE or SP stimulation. In contrast, lut and methlut are more effective MC inhibitors than cromolyn regardless of the trigger and the mediator measured.…”
Section: Discussionmentioning
confidence: 99%
“…17 Interestingly, some annexins without any secretory signals have been found in the extracellular space (e.g., annexin A1, A2, and A5 of human and annexin B1 of T. solium). 15,[18][19][20] The mechanism by which this occurs remains unclear and is worthy of investigation. 15,21 Recently, proteomic research on E. granulosus has shown that annexin B33 protein (Eg-ANX) could be detected in the excreted/secreted (ES) product and hydatid cyst fluid, which might potentially play important roles in parasite survival mechanisms during infection.…”
Section: Introductionmentioning
confidence: 99%
“…Originally described as an endogenous mediator of the anti-inflammatory effects of glucocorticoids, over the past 20 years, AnxA1 has been shown to have a broad range of molecular and cellular actions, including modulation of leukocyte migration in acute and chronic inflammation, kinase activities in signal transduction, preservation of cytoskeleton and extracellular matrix integrity, tissue maintenance, apoptosis, cell growth, and differentiation (1)(2)(3)(4)(5). AnxA1 is particularly abundant in cells of the myeloid lineage, including neutrophils, eosinophils, macrophages, and mast cells (6). In resting cells, AnxA1 is by and large localized in the cytosol, and upon activation, it can be secreted and then resynthesized.…”
mentioning
confidence: 99%